Penataan Pengelolaan Aparatur Sipil Negara (ASN) melalui Dynamic Governance (Jurnal Konstituen, 2019)
State Civil Apparatus Management (SCAM) is an activity to obtain quality, professional and clean ASN in realizing the implementation of public service tasks and the implementation of development for community welfare. To date, many experts have considered that the growing bureaucracy in Indonesia is a complicated, slow, inefficient and swollen bureaucracy. Dynamic governance can be used as a solution by: First, the government can explore the values and traditions that are local wisdoms. Second, the government can also learn from best practices in other countries, which can be learned and copied, to be developed in the bureaucracy in Indonesia. Likewise, the regional government can also learn from experiences and successes that have been carried out by other local governments, to be used as references to be adopted and developed in the areas where we are located. Third, change the paradigm and the wrong mindset of public service providers, which encourages a slow bureaucracy in Indonesia.